2019
DOI: 10.33070/etars.3.2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Development of Burners, Chambers, and Technologies for Reducing Emissions of Nitrogen Oxides by Boilers During the Combustion of Natural Gas

Abstract: In the article discusses the features of constructive solutions accepted in the burner devices and chambers of boiler units, which were used both when converting solid fuel boilers to natural gas, and creating new designs of gas boiler units. The works to reduce nitrogen oxide emissions at the Gas Institute of the National Academy of Sciences of Ukraine began in the 1960s and by 1971 significant results had been achieved was shown. The main methods and technical solutions that are used to reduce emissions of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Research carried out by the author (Sigal, 2004;Sigal & Bykorez, 2007;Sigal & Dolinsky, 2007;Sigal et al, 2019) have demonstrated that the nitrogen dioxide formation occurs in the pre-flame and post-flame zones at temperatures up to 1000 K.…”
Section: Analysis Of Publicationsmentioning
confidence: 99%
“…Research carried out by the author (Sigal, 2004;Sigal & Bykorez, 2007;Sigal & Dolinsky, 2007;Sigal et al, 2019) have demonstrated that the nitrogen dioxide formation occurs in the pre-flame and post-flame zones at temperatures up to 1000 K.…”
Section: Analysis Of Publicationsmentioning
confidence: 99%
“…In this context, developed countries, such as those identified in Figure 3a, stand out in the production of these technologies, which are being increasingly improved to meet current environmental demands. The control of the fuel/air reaction is one of these applicable processes, as well as technologies that promote the reduction of toxic gases, such as NOx, during combustion [59]. Thus, market growth in the field of industrial burners is expected by the year 2029, with compound annual growth rate (CAGR) projections of 4% during this period.…”
Section: Oec + Acousticmentioning
confidence: 99%
“…Кîíñòðóêц³я êîòлîàгðегàò³â òèпîðîçì³ð³â ТÂГ òà КÂГ çàâäяêè çàñòîñóâàííю äâîñâ³òíèõ еêðàí³â òà пîäîâèõ пàлüíèê³â çàбеçпе÷óє ³íòеíñèф³êàц³ю òеплîîбì³íó, çíèжеííя âèêèä³â îêñèä³â àçîòó äî çíà÷еíü â³äпîâ³äíî äî äèðеêòèâè ЄС äля ä³ю÷èõ êîòл³â, пðè цüîìó п³äòâеðäжеíèé ф³çè÷íèé ðеñóðñ êîòл³â ñêлàäàє б³лüш 40 ðîê³â [6,10,11]. Рàçîì ç òèì еêîíîì³÷íî îбґðóíòîâàíèì òà ìîжлèâèì є п³äâèщеííя ККÄ цèõ êîòл³â äî 94-96 % ó ðîбî÷îìó ä³àпàçîí³ їõ íàâàíòàжеííя çà ðàõóíîê ìîäеðí³çàц³ї ³ñíóю÷îї êîíâеêòèâíîї ÷àñòèíè (³ç çб³лüшеííяì плîщ³ її пîâеðõí³) òà óäîñêîíàлеííя пàлüíèêîâèõ пðèñòðîїâ.…”
Section: шляхи п³двищення òеплоòехн³чних òа еконоì³чних показник³в ко...unclassified